2018
DOI: 10.3390/rs10060853
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis Framework to Detect Key Environmental Factors Affecting Spatiotemporal Variability of Chlorophyll-a in a Tropical Productive Estuarine-Lagoon System

Abstract: Here, we demonstrate how a combination of three multivariate statistic techniques can identify key environmental factors affecting the seasonal and spatial variability of chlorophyll-a (Chl-a) in a productive tropical estuarine-lagoon system. Remote estimation of Chl-a was carried out using a NIR-Red model based on MODIS bands, which is highly consistent with the in situ measurement of Chl-a with root mean square error (RMSE) of 15.24 mg m −3 and 13.43 mg m −3 for two independent datasets used for the model's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…In the matter of degradation of chlorophyll-a, it may present absorbance similar to that observed in viable chlorophyll, which can generate reading errors. This high variance, however, is commonly observed in other chlorophyll-a studies using other methods in marine (Yaconi, 2006) and estuarine environments (Lins et al, 2018). A large number of studies in marine and estuarine contexts has shown that microphytobenthos are sensitive to environmental changes, because they obey daily rhythms of vertical migration, moving to the surface at low tide and descending at high tide (J. D. Palmer & Round, 1965;Round, 1979).…”
Section: Discussionmentioning
confidence: 95%
“…In the matter of degradation of chlorophyll-a, it may present absorbance similar to that observed in viable chlorophyll, which can generate reading errors. This high variance, however, is commonly observed in other chlorophyll-a studies using other methods in marine (Yaconi, 2006) and estuarine environments (Lins et al, 2018). A large number of studies in marine and estuarine contexts has shown that microphytobenthos are sensitive to environmental changes, because they obey daily rhythms of vertical migration, moving to the surface at low tide and descending at high tide (J. D. Palmer & Round, 1965;Round, 1979).…”
Section: Discussionmentioning
confidence: 95%
“…The positive correlation between areas that have higher WA and more critical trophic states can also be established from the study by Lins et al (2018). In this, the authors employed remote sensing techniques, together with measured reflectance and chlorophyll a data, to estimate the spatial-temporal variability of chlorophyll a, as well as the trophic state of MMELS, in the period of 2002 to 2016.…”
Section: The Wa and The Trophic State Indexmentioning
confidence: 94%
“…The results of coupling hydrological models and aquatic ecosystems, such as hydrodynamic models (Munar et al, 2018(Munar et al, , 2019 have highlighted their potential as management tools to understand and predict actions that cause future impacts on aquatic ecosystems. Remote sensing techniques applied to limnology studies have also been expanded to simulate watershed features and likely LULC changes over the years (Curtarelli et al, 2015;Lins et al, 2018;Ma et al, 2016).…”
Section: Novel Open Science Framework Based On Coupled Modelsmentioning
confidence: 99%